Olympic Education: from the Embodied Perspective - Bartle, Gillian (Πανεπιστήμιο Πελοποννήσου, 2015)
This thesis explores the concept of embodiment and suggests ways that the human being as embodied being might be viewed as central to the concept of Olympism. It also explores how this concept, in turn, might inform Olympic education. De Coubertin’s ‘starting point’ for his idea of Olympism was, arguably, internationalism and peace (Müller, 2004). Coupled with the notion of self-betterment, these features of Olympism are discussed in depth as they inform contemporary debate on Olympic education. In order to fulfil enrichment of current Olympic education programmes, it is suggested that a deeper philosophical understanding of the human being is required. Such understanding refers to the concept of ‘human being as moving being’ (Martίnková, 2011, 2012). It is also suggested that individual self-betterment relies on intersubjective interaction (Rintala, 1994; Simon, 2000; McLaughlin & Torres, 2011). Central to the success of this interaction is the embodied being (Whitehead, 1987, 2010). It is argued that embodiment ought to be placed as central to the idea of Olympism through participation in competitive sport at all levels (Whitehead, 2010). This thesis concludes by discussing the implications of the universalisability of the embodiment and intersubjective interaction based on empathy, for Olympism and for pedagogies that inform Olympic education programmes.
Keywords: Olympic education - Curriculum; Physical education and training; Olympism - Philosophy; Ολυμπιακή εκπαίδευση - Πρoγράμματα; Φυσική αγωγή και εκπαίδευση; Ολυμπισμός - Φιλοσοφία; Olympic Education; Self-betterment; Embodiment; Internationalism; Peace; Ολυμπιακή Παιδεία; Αυτοβελτίωση; Ενσάρκωση; Διεθνισμός; Ειρήνη